Health risks of essential Cu and Zn via consumption of water spinach Ipomoea aquatica collected fro Peninsular Malaysia - Yap, Chee Kong; Cheng, Wan Hee; Wong, Koe Wei; Yaacob, Aziran; Razalai, Rozilah; Leow, Chee Seng; Peng, Shih Hao Tony; Ismail, Mohamad Saupi; Yap, Chee Wah; He, Yuhai; Sharifinia, Moslem; Bakhtiari, Alireza Riyahi; et al. (2019)
The concentrations of Fe and Ni were analyzed in the water spinach Ipomoea aquatica collected from 11 sampling sites (Ara Kuda (2016), Setiawan (2016), Sikamat (2013-2018) and 8 sites in Sepang area (2005-2006)) from Peninsular Malaysia. The range of Fe (mg/kg dw) in the plant samples was 155-775(15.5-77.5mg/kg ww) while the range of Ni(mg/kg dw) was 1.71-20.3(0.17-2.03 mg/kg ww). In assessing the human health risk, the target hazard quotient values for Fe and Ni in Malaysian adults are <1.00. The current results showed no non-carcinogenic risks of Fe and Ni through the consumption of I. aquatica from the 11 sites. Considering the fact that most of the samples were collected from the wild and grown in the uncontrolled drainages, the heavy metal concentrations should be closely monitored in these vegetables.